KONSTRUKSI INSTALASI PIPA MIGAS BAWAH LAUT DI TELUK BALIKPAPAN - Sulardi Sulardi (Universitas Lambung Mangkurat, 2021)
The purpose of this study is to describe the use of material specifications and methods for the construction of underwater oil and gas pipeline installations. This research uses an applied research method with a case study approach in the context of replacing an underwater oil and gas pipeline from the North Penajam Paser coast to the Balikpapan refinery. The results of the research that can be achieved are that the 399 meter long underwater pipe has been replaced with standard API 5L Grade X52 carbon steel specifications and the large lay method by maximizing pipe welding and technical inspection of the welding results on board. Based on the results of this study, it is also recommended that the material specifications and working methods of underwater pipe installation construction work well are applied in similar work areas.